Preface [Advances in evolutionary and deterministic methods for design, optimization and control in engineering and sciences] - Gaspar-Cunha, A. (2021)
[Excerpt] This book contains book chapters from selected and extended contributions presented at the EUROGEN 2019 International Conference, that took place at the University of Minho at the historical town of Guimarães in the north of Portugal on September 12-14, 2019. EUROGEN 2019 was the 13th of a series of International Conferences previously held in Las Palmas de Gran Canaria (1995), Trieste (1997), Jyväskylä (1999), Athens (2001), Barcelona (2003), Munich (2005), Jyväskylä (2007), Kracow (2009), Capua (2011), Las Palmas de Gran Canaria (2013), Glasgow (2015) and Madrid (2017) mainly focused on Evolutionary and Deterministic Computing for Industrial Applications. This conference aims at bringing together specialists from universities, research institutions and industries developing or applying evolutionary and deterministic methods in design optimization and control and emphasizing industrial and societal applications. This series of conferences was originally launched by the EC –Strategic/Prospective Network INGENET in 1998. EUROGEN 2019 is, also, an ECCOMAS Thematic Conference also co-ordinated by the Special Interest Group (SIG) with ERCOFTAC (European Research Community on Flow, Turbulence and Combustion). The conference included the following topics: metaheuristics and evolutionary algorithms, multiobjective evolutionary algorithms and constraint handling techniques, adjoint-based including oneshot methods, hybrid optimisation methods, high-performance computing, goal-oriented optimization for mesh and meshless methods, game strategies, surrogate models for optimisation, parallel and distributed evolutionary algorithms, multi-disciplinary optimization methods, design optimization under uncertainties, multi-criteria decision making and topology optimization. [...]